Detection of interictal epileptiform discharges using signal envelope distribution modelling: application to epileptic and non-epileptic intracranial recordings - Janca, Radek; Jezdik, Petr; Cmejla, Roman; Tomasek, Martin; Worrell, Gregory A; Stead, Matt; Wagenaar, Joost; Jefferys, John G R; Krsek, Pavel; Komarek, Vladimir; Jiruska, Premysl; Marusic, Petr (Brain topography, 2015)
Interictal epileptiform discharges (spikes, IEDs) are electrographic markers of epileptic tissue and their quantification is utilized in planning of surgical resection. Visual analysis of long-term multi-channel intracranial recordings is extremely laborious and prone to bias. Development of new and reliable techniques of automatic spike detection represents a crucial step towards increasing the information yield of intracranial recordings and to improve surgical outcome. In this study, we designed a novel and robust detection algorithm that adaptively models statistical distributions of signal envelopes and enables discrimination of signals containing IEDs from signals with background activity. This detector demonstrates performance superior both to human readers and to an established detector. It is even capable of identifying low-amplitude IEDs which are often missed by experts and which may represent an important source of clinical information. Application of the detector to non-epileptic intracranial data from patients with intractable facial pain revealed the existence of sharp transients with waveforms reminiscent of interictal discharges that can represent biological sources of false positive detections. Identification of these transients enabled us to develop and propose secondary processing steps, which may exclude these transients, improving the detector's specificity and having important implications for future development of spike detectors in general.
Keywords: Electroencephalography; Male; elektroencefalografie; senzitivita a specificita; Algorithms; Epilepsy; implantované elektrody; Electrodes, Implanted; False Positive Reactions; Humans; Facial Pain; algoritmy; Signal Processing, Computer-Assisted; mužské pohlaví; Female; mladiství; rozpoznávání automatizované; chronická bolest; Pattern Recognition, Automated; ženské pohlaví; falešně pozitivní reakce; obličejová bolest; mozek; mladý dospělý; Adult; Principal Component Analysis; Young Adult; počítačové zpracování signálu; falešně negativní reakce; Sensitivity and Specificity; epilepsie; Adolescent; Brain; dospělí; dítě; lidé; Chronic Pain; Child; False Negative Reactions; analýza hlavních komponent